Implementation of North Sumatra Provincial Regulation No. 3 of 2014 concerning the Implementation of Child Protection Against Differences in Beliefs/Religions Adhered to by Children from the Perspective of Siyasah Dusturiyah - Harahap, Syakirah Alda; Khalid, Khalid (LEGAL BRIEF, 2025)
This study aims to analyze the implementation of Regional Regulation of North Sumatra Province No. 3 of 2014 on Child Protection, particularly in safeguarding children who experience violence due to religious differences or religious conversion, through the lens of Fiqh Siyasah Dusturiyah. This research employs a normative-empirical legal method, combining statutory, conceptual, and empirical approaches, with data obtained from legislative review and interviews with relevant local government institutions. The case study focuses on a 15-year-old girl named Dewi, who faced physical and psychological violence from her father in 2023 after converting from Christianity to Islam. The findings reveal that the regulation is implemented mostly in administrative terms and lacks substantive legal enforcement. From the perspective of Fiqh Siyasah Dusturiyah, the state should act as a guardian of justice and protector of maq??id al-shar?'ah. Therefore, this study recommends a policy reform grounded in constitutional justice and Islamic benefit values to ensure comprehensive protection of children's spiritual rights and physical safety